Media ethics : issues and cases - Philip Patterson, Lee C. Wilkins, Chad Painter; Patterson, Philip; Wilkins, Lee C., 1949-; Painter, Chad, 1977- (U.K Rowman & Littlefield Publishing, 2019)
"The ninth edition of Media Ethics: Issues and Cases has been updated to reflect the most pressing ethical issues in media. Featuring 25 new cases on hot topic issues from fake news to drones and a new chapter on social justice, this authoritative case book gives students the tools to make ethical decisions in an increasingly complex environment"--
An introduction to ethical decision making -- Information ethics : a profession seeks the truth -- Strategic communication: does client advocate mean consumer adversary? -- Loyalty : choosing between competing allegiances -- Privacy : looking for solitude in the global village -- Mass media in a democratic society : keeping a promise -- Media economics : the deadline meets the bottom line -- Picture this : the ethics of photo and video journalism -- Informing a just society -- The ethical dimensions of art and entertainment -- Becoming a moral adult.
Includes bibliographical references and index.
Keywords: Mass media -- Moral and ethical aspects; Communication -- Moral and ethical aspects